Not by bread alone: Estimating potato demand in India in 2030 - Scott, G. J.; Petsakos, Athanasios; Suarez, V. (Springer, 2019)
While much of the literature on future food consumption in India in the decades ahead focuses on cereals, this paper presents estimates of potato demand to the year 2030 according to three different scenarios. Estimated increases in total food demand for potato range from 20 to 30 million metric tonnes and from 5.5 to 15 kg capita−1 year−1, with modest, if any, increases in foreign trade. These estimates highlight the potato’s growing importance in Indian diets as food consumption patterns continue to evolve while maintaining their traditional roots. They also call for a series of public and private initiatives to facilitate the realization of the potato’s potential future contribution to food consumption and nutrition in India. These include renewed support for research and development as relates to improved technologies for the potato sector both on and off the farm. It also involves opportunities for industry to combine market-driven innovations to achieve commercial success with benefits for growers, consumers and the environment as well.